THE IMPACT OF INVESTMENTS, EXPORTS, AND OPENNESS ON ECONOMIC GROWTH. A COMPARATIVE STUDY ON THE EAST EUROPEAN COUNTRIES - Simuţ Ramona (Annals of the University of Oradea: Economic Science, 2012)
The study of the economic growth process has older implications. The preoccupation for the study of the economic growth has existed beginning with the representatives of the Classical School and continuing with the Keynesians, Neokeynesians, and Neoclassics. A series of empirical studies have tested the correlation between the dynamics of the different factors and the process of economic growth. \r\nThis paper examines the role of investments, export and openness in relation to economic growth for the East European countries and also has the objective to estimate the long-run relationship between economic growth, investment and export in Eastern European countries using trimestrial data from the Eurostat as well as National Statistical Institute. We used Johansen cointegration test to estimate the nature of relationship and Granger causality test is used to determine the direction of causality in the model.\r\n